Numerical Experimental Comparison of Dam Break Flows with non-Newtonian Fluids - Minussi, Roberta Brondani; Maciel, Geraldo de Freitas [UNESP] (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2012)
The dam-break flow involving non-Newtonian fluids is a type of flow commonly observed in nature as well as in common industrial processes. Experiments of non-Newtonian dam-break flows were conducted in horizontal channels and aqueous solutions of Carbopol 940 were used, which were modeled by the Herschel-Bulkley constitutive equation. Their flows were filmed and the frames were compared with numerical simulations. Two particular results were analyzed: the front wave evolution with time and its stop distance. The CFX software was employed and the simulations were conducted with the VOF method. Both results, numerical and experimental, were compared with shallow water approximation solutions found in literature. The numerical code, which uses complete momentum equations, showed better agreement with the experiments than those using shallow water equations. It seems that the hypotheses used by the shallow water approximated equations are not appropriate for the first instants of the flow, just after the dam-break and errors are introduced. Probably, these errors are propagated producing the differences encountered.
Keywords: dam-break; Herschel-Bulkley fluids; shallow water; complete solution; VOF